FATTY ACID PROFILE ANALYSIS OF KARUPU KAVUNI RICE (Oryza sativa L. indica) BY USING GC- MS/ FID - TNA, ARUNASREE; BHUVANA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The FAME (Fatty acid Methyl esters) analysis identifies the fatty acids group. In this study the karupu kavuni rice is examined for the analysis of fatty acid methyl esters by using the GC-MS/FID. The chromatogram showed 11 major fatty acids at the different peak heights. The highest peak chromatogram was found at the retention time of 17.6 min, and the fatty acid was identified as omega-6-fatty acid. The amount of unsaturated fatty acid is high when compared to the saturated fatty acid group in kavuni rice. Hence the karupu kavuni rice is enriched with high good triglycerides which effectively act as the precursor for the various types of the life style diseases.